Zagrożenia dla polskich uniwersytetów - Drozdowicz, Zbigniew (NAUKA Polska Akademia Nauk, 2016)
In these remarks I undertake attempts to point out some significant threats for Polish universities – such as threats for fulfilling by those institutions their social mission, creating their scientific greatness, or maintaining and developing their traditional freedom. The problem lies not in the fact that these threats are today not observed by the academic milieu, but more in the fact that they are often belittled or judged in such a way that it give very little chance to defend oneself against them. The problem lies also in the fact that it is difficult such safety measures against them which could successfully applied at al Polish universities. In those remarks I do not make an attempt to point out such safety measures anyway. However, some of my remarks might contribute to a more effective search for them.
Keywords: threats to the essence of university; university's greatness and freedom